Early-life respiratory viral infections, atopic sensitization, and risk of subsequent development of persistent asthma - Kusel, Merci M.H.; de Klerk, Nicholas H.; Kebadze, Tatiana; Vohma, Vaike; Holt, Patrick G.; Johnston, Sebastian L.; Sly, Peter D. (Journal of allergy and clinical immunology, 2007)
Severe lower respiratory infections (LRIs) and atopic sensitization have been identified as independent risk factors for asthma. The nature of potential interactions between these risk factors was the subject of this study. A community-based cohort of 198 children at high atopic risk was followed from birth to 5 years. All episodes of acute respiratory illness in the first year were recorded and postnasal aspirates were collected for viral identification. History of wheeze and asthma was collected annually, and atopy was assessed at 6 months, 2 years, and 5 years. A total of 815 episodes of acute respiratory illness were reported, and 33% were LRIs. Viruses were detected in 69% of aspirates, most commonly rhinoviruses (48.3%) and respiratory syncytial virus (10.9%). At 5 years, 28.3%(n = 56) had current wheeze, and this was associated with wheezy [odds ratio (OR), 3.4 (1.2-9.7); P = .02] and/or febrile LRI [OR, 3.9 (1.4-10.5); P = .007], in particular those caused by respiratory syncytial virus or rhinoviruses [OR, 4.1 (1.3-12.6); P = .02]. Comparable findings were made for current asthma. Strikingly these associations were restricted to children who displayed early sensitization (≤2 years old) and not observed in nonatopic patients or those sensitized later. These data suggest viral infections interact with atopy in infancy to promote later asthma. Notably the occurrence of both of these events during this narrow developmental window is associated with maximal risk for subsequent asthma, which suggests a contribution from both classes of inflammatory insults to disease pathogenesis. Protection of “high-risk” children against the effects of severe respiratory infections during infancy may represent an effective strategy for primary asthma prevention. The potential benefits of these strategies merit more careful evaluation in this age group.